2010
DOI: 10.1002/adsc.201000554
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Asymmetric Hydrogenation of Simple Ketimines Using a Brønsted Acid as Activator

Abstract: Using a catalytic amount of a Brønsted acid as activator of simple imines, the highly enantioselective homogeneous palladium-catalyzed asymmetric hydrogenation of simple ketimines was successfully developed with up to 95% ee.Keywords: asymmetric hydrogenation; Brønsted acids; ketimines; palladium catalysisThe preparation of chiral amines from the transition metal-catalyzed asymmetric hydrogenation or transfer hydrogenation of prochiral imines represents one of the most direct and efficient approaches that open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 71 publications
1
19
0
1
Order By: Relevance
“…14 Within these methods, the homogeneous transition metal-catalyzed oxidative dehydrogenation of alcohols to carbonyl compounds that can form an imine by condensation with an amine is an attractive synthetic approach due to high atom efficiency. [15][16][17][18][19] Nevertheless, these homogeneous catalysts suffer from drawbacks such as difficulty in recovery and reuse of expensive metals, necessity of special handling of metal complexes, and the required use of co-catalysts such as a base promoter and a stabilizing ligand. Hence, the application of efficient, easily recoverable heterogeneous catalysts which are relatively inexpensive, would clearly be advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…14 Within these methods, the homogeneous transition metal-catalyzed oxidative dehydrogenation of alcohols to carbonyl compounds that can form an imine by condensation with an amine is an attractive synthetic approach due to high atom efficiency. [15][16][17][18][19] Nevertheless, these homogeneous catalysts suffer from drawbacks such as difficulty in recovery and reuse of expensive metals, necessity of special handling of metal complexes, and the required use of co-catalysts such as a base promoter and a stabilizing ligand. Hence, the application of efficient, easily recoverable heterogeneous catalysts which are relatively inexpensive, would clearly be advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, Norton demonstrated the first catalytic enantioselective hydrogenation of N-benzylimine through an ionic mechanism with the assistance of HBF 4 and achieved 66% ee [118]. Later, it was reported that the introduction of an acid activator could be achieved by preforming iminium type substrates such as N-H imines [43,119], or by the addition of the acid activator in situ [120,121]. Following that strategic breakthrough, groundbreaking works of Pd-catalyzed asymmetric hydrogenation of heteroaromatics, such as unprotected indoles by Zhou et al, and pyrroles by Zhou, Fan et al were recently published [115,122,123].…”
Section: Inhibitory Effect Of Amine Product and Activation Strategymentioning
confidence: 97%
“…Using Pd(CF 3 COO) 2 as the Pd precursor, in TFE, C 4 -TunePhos was found to be the most effective biaryl diphosphine ligand in affording the corresponding chiral amines at up to 95% ee (Scheme 39) [120]. A series of Brønsted acid studied in this reaction and D-DTTA was found to be the best additive in terms of enantioselectivity.…”
Section: Inhibitory Effect Of Amine Product and Activation Strategymentioning
confidence: 97%
See 1 more Smart Citation
“…25 The addition of Brønsted acid could not only play a great part in the activation of the substrate, but also reduce the inhibitory effect of the substrate on the palladium catalyst the same as the electron-withdrawing group played. Interestingly, this protocol was more effective for the asymmetric hydrogenation of ketimines derived from tetralone than that from simple acetophenones (Scheme 9).…”
mentioning
confidence: 99%